A comparative study on the health status of caregivers between intensive and non-intensive care unit patients in a tertiary care hospital of urban Bengaluru - Ramesh Masthi, N. R.; S, Laveena; Sharmila, M.; Kumari, Nitu; A., Aparna; G., Divya Bharathi (International Journal Of Community Medicine And Public Health, 2021)
Background: Caregivers providing care to hospitalized family members are potentially at risk for declining physical and psychological health. To assess and compare physical and psychological burden of caregivers of Intensive care unit and non-Intensive care unit (non-ICU) patients. Methods: A descriptive, hospital-based, cross-sectional study was conducted among 256 caregivers (127 Intensive care unit and 129 non-ICU patients) in a tertiary care hospital in urban Bengaluru for 6 months (July-December, 2019). A modified Hospital anxiety and depression scale (HADS) and Perceived stress scale was used to assess the anxiety and stress burden among the caregivers, respectively. Results: Out of 256 caregivers, 196 (76.56%) experienced some form of physical burden, 112 (57.14%) belonged to ICU group and 84 (42.86%) non-ICU group (Z=2, p=0.045). Anxiety problem was observed in 54.29% caregivers, and was found statistically significant in caregivers of ICU (62.59%) patients than non-ICU (37.41%) patients (Z=2.969, p=0.002). Similarly, the burden of stress was observed in 203 (79.29%) caregivers, predominantly in ICU group (54.19%) compared to non-ICU (45.81%) group. Conclusions: Three-fourth of the caregivers had one or the other physical symptoms and nearly half of them had stress and anxiety irrespective of ICU or non-ICU admission. The financial burden was more among the ICU caregivers and the longer duration of stay had affected the health of the caregivers.